Why regions? - Manuel Pastor; William Lester; Justin Scoggins (University of California, Institute of Urban and Regional Development (IURD), 2007)
The past decade has seen a resurgence of interest in the idea of regionalism, that is, the basic notion that economic trends, social challenges, and environmental problems are not neatly contained by city jurisdictions and that solutions must thus incorporate coalitions and constituencies from across the metropolitan landscape. Such interest is, of course, not entirely novel: discussions about thinking, planning, and acting regionally have waxed and waned since Daniel Burnham's 1909 Plan for Chicago stressed the need for infrastructure improvements and transportation investments at the regional rather than urban scale. But part of what seems to make the new regionalism both new and real is that the rising interest is not confined to planners and academics: alongside the scholarly literature has come a body of practice, including the engagement of business and political leadership in metropolitan organizations like the business-oriented Chicago 2020, the evolution of community-oriented metropolitan groups like the Los Angeles Alliance for a New Economy, and the growing presence of new regionally-focused intermediaries like the Alliance for Regional Stewardship, PolicyLink, Smart Growth America, and many others.
Keywords: 330